2020
DOI: 10.21203/rs.3.rs-59493/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extended Adverse Effects of Cyclophosphamide on Mouse Ovarian Function

Abstract: Purpose: Most patients with cancer undergo multiple administrations of anticancer drugs during treatment, resulting in chronic impairment of their reproductive health. As improved treatment options increase cancer survival, it has become increasingly important to address fertility issues in cancer survivors. In this study, we examined the pathophysiological effects of multiple exposures to cyclophosphamide (Cy) on the ovaries of mice and their underlying molecular mechanism. Methods: C57BL/6 mice were intraper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The cumulative dose in most patients did not exceed 3 grams and its dose was not dependent on the body weight. Kim et al mentioned that the cumulative exposure to CYC should be reduced, as 15-20 grams may cause infertility in >50% of females >30 years, and the risk is lower in younger patients [7].…”
Section: Avn (Avascular Hip Necrosis) CMV (Cytomegalovirus) Cyc (Cycl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative dose in most patients did not exceed 3 grams and its dose was not dependent on the body weight. Kim et al mentioned that the cumulative exposure to CYC should be reduced, as 15-20 grams may cause infertility in >50% of females >30 years, and the risk is lower in younger patients [7].…”
Section: Avn (Avascular Hip Necrosis) CMV (Cytomegalovirus) Cyc (Cycl...mentioning
confidence: 99%
“…The adverse effects of CYC include leucopenia, infection, hemorrhagic cystitis, gonadal toxicity, infertility, and teratogenicity [7], but Luo et al reported that the main adverse effects of CYC and MMF were infection and gastroenteritis [8]. Khattab et al reported that CYC had much less cost in comparison to MMF, with no difference in efficacy, safety profile, or quality of life [9].…”
Section: Introductionmentioning
confidence: 99%